Girard and the Spaces of Apocalyptic - O'Regan, Cyril (Modern theology, 2012)
This article examines the apocalyptic turn evident in René Girard's Battling to the End (2009), which puts an exclamation point on what has been an increasing tendency in Girard's thought. Its general aim is to describe Girard's particular form of biblical apocalyptic. Toward that end, (a) it unfolds Girard's arguments against other apocalyptic contenders, including Hegel and Heidegger; (b) it opens up a space of conversation with other forms of apocalyptic thought (e.g. Johann Baptist Metz and, more controversially, Emmanuel Levinas); and (c) in and through Girard's affirmation of Benedict XVI, raises the question of whether there is a structural symmetry between their thought, and whether both articulate a form of Augustinian apocalyptic.